2019
DOI: 10.1017/s1047951119000398
|View full text |Cite|
|
Sign up to set email alerts
|

Living the heart in three dimensions: applications of 3D printing in CHD

Abstract: Advances in biomedical engineering have led to three-dimensional (3D)-printed models being used for a broad range of different applications. Teaching medical personnel, communicating with patients and relatives, planning complex heart surgery, or designing new techniques for repair of CHD via cardiac catheterisation are now options available using patient-specific 3D-printed models. The management of CHD can be challenging owing to the wide spectrum of morphological conditions and the differences between patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…The benefits of 3D models in clinical practice have been demonstrated by several authors. It is a useful tool for preoperative planning and trainee education of complex congenital cardiac, thoracic and abdominal cases 6,8,11 . Jones et al 7 observed that when 3D models were printed for anatomic abnormalities (like vascular rings or pulmonary artery sling) and, subsequently used by young cardiothoracic surgeons for learning, it was a better comprehension of the surgical anatomy of all cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The benefits of 3D models in clinical practice have been demonstrated by several authors. It is a useful tool for preoperative planning and trainee education of complex congenital cardiac, thoracic and abdominal cases 6,8,11 . Jones et al 7 observed that when 3D models were printed for anatomic abnormalities (like vascular rings or pulmonary artery sling) and, subsequently used by young cardiothoracic surgeons for learning, it was a better comprehension of the surgical anatomy of all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of the patient‐specific model, the advantages of 3D printing have been demonstrated in different forms of CHD. This innovative technology has helped the clinicians by the possibility to personalized treatments, particularly in complex cases as double outlet right ventricle or pulmonary venous return malformation 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations